(untitled) (Scientific journal of the Fergana State University, 2025)
This paper explores the diverse methodologies employed in foreign language teaching (FLT), examining their effectiveness in fostering language acquisition and communicative competence. It analyzes various pedagogical approaches, including communicative language teaching (CLT), grammar-translation, task-based learning, and technology-integrated methods, considering their strengths and weaknesses in developing different aspects of language proficiency (reading, writing, listening, and speaking). The study also considers the influence of learner characteristics (learning styles, motivation, prior language experience) and contextual factors (teacher training, resource availability, learning environment) on the success of different FLT methodologies. By reviewing existing research and identifying best practices, the paper aims to provide insights for educators and policymakers seeking to optimize FLT approaches to enhance language learning outcomes and promote effective communication skills.